Formulation of dusty micropolar fluid mathematical model - Anisah, Dasman; Nur Syamilah, Arifin; Abdul Rahman, Mohd Kasim; Yacob, N A (IOP Publishing, 2019)
Dusty micropolar fluid model is a new generation of fluid model that is embedded with the dust particles which having micro rotation behavioural. The proposed model will incorporate with thermal boundary condition known as Newtonian heating (NH). This paper aims to present the details of formulation on mathematical model of dusty micropolar fluid starting with its basic equations until obtaining a set of solvable form of equations. The derivation of equations involves two set of equations which covering the fluid and dust phases respectively. In order to decrease the complexity, the respective model will be undergoing the suitable similarity transformations to transform the equations into the solvable form. The numerical solution presented by compared with previous study to check the validity of the model. The resulting equation will give advance understanding on dusty micropolar fluid model to the researchers especially mathematician and fluid mechanist.